Inside Cover: Oxidative Transformations of Biosourced Alcohols Catalyzed by Earth‐Abundant Transition Metals (ChemCatChem 14/2017). Issue 14 (24th July 2017) - Nguyen, Duc Hanh; Morin, Yohann; Zhang, Lei; Trivelli, Xavier; Capet, Frédéric; Paul, Sébastien; Desset, Simon; Dumeignil, Franck; Gauvin, Régis M.
Abstract : The Cover illustrates the conversion of alcohols into carboxylic acid salts using base‐metal pincer catalysts.In their Full Paper, D. H. Nguyen et al. demonstrate that the catalytic acceptorless dehydrogenative oxidation of biosourced alcohols into carboxylic acid salts can be achieved in good to excellent yields thanks to aliphatic earth‐abundant Fe‐ and Mn‐PNP complexes, with release of H2 as the sole by‐product. Attempts to generate aldehydes from alcohols were not successful using the Fe and Mn species, but a commercially available Ru analogue achieves this transformation selectively under very mild conditions in the presence of a large excess of acetone as a hydrogen acceptor. More information can be found in the Full Paper by D. H. Nguyen et al. (onpage 2652 in Issue 14, 2017 DOI:10.1002/cctc.201700310 ).